A study to evaluate urine albumin-creatinine ratio (UACR) for albuminuria in patients with sepsis admitted to medicine department in RL Jalappa Hospital and its correlation with Sequential Organ Failure Assessment (SOFA) score - K Harshitha, K Harshitha; C R, Vidyasagar; Manjunatha N, Manjunatha N; Prabhavathi K, Prabhavathi K (Journal of Neonatal Surgery, 2025)
Background In critical care, it is crucial to anticipate death in critically ill sepsis patients early and to start aggressive therapy as soon as possible. This study is to demonstrate the potential function of UACR as a measure of renal dysfunction and total organ failure by comparing it with the SOFA score in septic patients. Material and Methods A cross sectional study was undertaken in 30 patients admitted to intensive care. At the time of admission, the Glasgow coma scale was used to evaluate each patient's level of consciousness. The GCS scores were used to grade the severity of the condition. Urine microalbumin was measured using the immunoturbidometric method and creatinine was measured using the Jaffe method from spot urine samples that were taken within six hours of admission. When each patient was admitted, their qSOFA was calculated along with their urine microalbumin: creatinine ratio, or UACR. Results Average albumin levels in urine 50% of the cases in this study had UACRs between 30 and 300, and the creatinine ratio at admission was 92.93. At 24 hours, the urine albumin creatinine ratio was 96.97, and 56.7% of the cases had a UACR between 30 and 300. In this study, there was a substantial positive connection between SOFA scores at admission and 24 hours later and UACR at admission and 24 hours. Conclusion According to this study, the UACR test can predict the survival of sepsis patients admitted to the critical care unit. Additionally, it can track how well therapy interventions are working.